The Digital Product Passport (DPP): A Technological Framework for Secure, Interoperable, and Circular Supply Chain Transformation (International Journal of Scientific Research in Science and Technology, 2025)
The Digital Product Passport (DPP) redefines product transparency by digitally capturing vital data on origin, composition, and lifecycle. This innovation empowers consumers to make informed, sustainable choices and drives accountability across value chains. DPPs facilitate circular economy practices by supporting repair, reuse, and recycling through verified, accessible product histories. For businesses, DPP adoption diminishes counterfeiting, simplifies compliance, and builds regulatory trust. Seamless data sharing between stakeholders fosters industry collaboration and efficiency. While deployment challenges exist, the DPP’s potential to revolutionize sustainability, supply chain traceability, and consumer engagement is immense.